2016
DOI: 10.1016/j.jpeds.2015.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic Altitude-Induced Cognitive Dysfunction in Children and Adolescents

Abstract: Acute short-term exposure to an altitude at which major tourist destinations are located induces marked executive and memory deficits in healthy children. These deficits are equally marked or more severe in children permanently living at high altitude and are expected to impair their learning abilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…Verbal and spatial WM are both reportedly impaired in HA residents (Yan et al, , ); however, the impact of HA on the executive system has not been elucidated. Previous study using the Go/NoGo and the Trail Making Test (part B) tasks showed that inhibition and shifting processes were affected in HA residents (Ma, Wang, Wu, Luo, & Han, ; Rimoldi et al, ). It remains unclear whether the updating process is involved in WM impairment.…”
Section: Introductionmentioning
confidence: 98%
“…Verbal and spatial WM are both reportedly impaired in HA residents (Yan et al, , ); however, the impact of HA on the executive system has not been elucidated. Previous study using the Go/NoGo and the Trail Making Test (part B) tasks showed that inhibition and shifting processes were affected in HA residents (Ma, Wang, Wu, Luo, & Han, ; Rimoldi et al, ). It remains unclear whether the updating process is involved in WM impairment.…”
Section: Introductionmentioning
confidence: 98%
“…; Rimoldi et al . ; McMorris et al . ), including lasting damage to white and grey matter motor architecture (Di Paola et al .…”
Section: Introductionmentioning
confidence: 99%
“…The requirement to process large amounts of O 2 over a relatively small tissue mass supports the high rate of ATP formation to fuel the maintenance of ionic equilibria and uptake of neurotransmitters for synaptic transmission (Alle et al 2009). That cognitive function is impaired by acute hypoxia is thus not surprising and an extensive literature has since documented proportional deficits in executive function, attention, mental speed, language and memory (Virues-Ortega et al 2004;Rimoldi et al 2016;McMorris et al 2017), including lasting damage to white and grey matter motor architecture (Di Paola et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In air conditioning is the refrigerant gas in chiller, in oxygen-conditioning is zeolite to absorb nitrogen from atmospheric air [77]. Possible more general applications may be schools because the learning is compromised at high altitudes [78], hospitals (since, for example, wound healing is compromised at great heights and neonatal mortality is higher [79][80][81], boardrooms, courts, banks and embassies [62].…”
Section: Non-conventional Indicationsmentioning
confidence: 99%